2019
DOI: 10.1073/pnas.1903506116
|View full text |Cite
|
Sign up to set email alerts
|

Wnt canonical pathway activates macropinocytosis and lysosomal degradation of extracellular proteins

Abstract: Canonical Wnt signaling is emerging as a major regulator of endocytosis. Wnt treatment markedly increased the endocytosis and degradation in lysosomes of BSA. In this study, we report that in addition to receptor-mediated endocytosis, Wnt also triggers the intake of large amounts of extracellular fluid by macropinocytosis, a nonreceptor-mediated actin-driven process. Macropinocytosis induction is rapid and independent of protein synthesis. In the presence of Wnt, large amounts of nutrient-rich packages such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 64 publications
7
99
0
Order By: Relevance
“…Wnt activation is known to induce endocytosis of the receptor complex (11,12). We confirmed that Lrp6 endocytosis was observed in SW480, a colon cancer cell line in which the absence of APC triggered, and APC reconstitution inhibited, Wnt signaling and Lrp6 endocytosis (SI Appendix, Movie S1); this is in agreement with recent results showing that APC is a major regulator of endocytosis (16,29). As expected for regulators of Lrp6 endocytosis, the Wnt antagonists Dkk1 (30) or Bighead (31) induced endocytosis of Lrp6-APEX2 into large vesicle clusters in the cytoplasm next to the nuclear bay region, where the lysosomal system is located Fig.…”
Section: Lrp6-apex2 Receptor Fusion Is Active In Wnt Signalingsupporting
confidence: 91%
See 2 more Smart Citations
“…Wnt activation is known to induce endocytosis of the receptor complex (11,12). We confirmed that Lrp6 endocytosis was observed in SW480, a colon cancer cell line in which the absence of APC triggered, and APC reconstitution inhibited, Wnt signaling and Lrp6 endocytosis (SI Appendix, Movie S1); this is in agreement with recent results showing that APC is a major regulator of endocytosis (16,29). As expected for regulators of Lrp6 endocytosis, the Wnt antagonists Dkk1 (30) or Bighead (31) induced endocytosis of Lrp6-APEX2 into large vesicle clusters in the cytoplasm next to the nuclear bay region, where the lysosomal system is located Fig.…”
Section: Lrp6-apex2 Receptor Fusion Is Active In Wnt Signalingsupporting
confidence: 91%
“…Here, we describe the results obtained with a Human Embryonic Kidney 293T (HEK293T) cell line stably expressing a chimeric Lrp6-APEX2 receptor. Our proteomic data indicate that in presence of Wnt3a, the Lrp6-interactome was enriched in components of the ESCRT machinery that forms MVBs, providing independent support to our previous findings that endocytosis is at the core of Wnt pathway intracellular regulation (11,15,16). We also discovered that Tropomyosin-receptor kinase fused gene (Trk-fused gene, TFG), a protein involved in several pathologies including cancer (26), was a highly enriched target of Wntactivated Lrp6-APEX2 and localized to endosomal vesicles.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Next we aimed to determine the mechanism of macropinocytosis induction downstream of ATM inhibition. Towards this goal, we used pharmacological or genetic inhibition of PI3K/AKT, WNT, and AMPK, three known inducers of macropinocytosis (Commisso et al, 2013;Kim et al, 2018;Redelman-Sidi et al, 2018;Tejeda-Munoz et al). While inhibition of PI3K, AKT, or WNT had no effect ( Fig.…”
Section: Inhibition Of Atm Kinase Activity Induces Macropinocytosis Tmentioning
confidence: 99%
“…Macropinocytosis is an endocytic process whereby cells take up fluid, macromolecules, metabolites, and other cargo from the surrounding microenvironment (King and Kay, 2019;Palm, 2019;Zhang and Commisso, 2019). Many studies have evaluated the critical role of macropinocytosis as a nutrient scavenging mechanism in cancers under nutrientdeprived conditions (Commisso et al, 2013;Davidson et al, 2017;Hodakoski et al, 2019;Kamphorst et al, 2015;Kim et al, 2018;Redelman-Sidi et al, 2018;Tejeda-Munoz et al;Yao et al, 2019). To date, these studies have focused on cancers with high PI3K activity, such as those with mutant RAS or PTEN loss, which act upstream of the Rac1-Pak1 actin remodeling pathway to promote macropinosome formation .…”
Section: Introductionmentioning
confidence: 99%